THE IMPLEMENTATION OF ROLE-PLAY IN TEACHING SPEAKING FOR EFL LEARNERS (Jurnal Bahasa Lingua Scientia, 2024)
The language that is almost used in international communication is English. In terms of speaking, EFL learners still have a lot of difficulties, which make that interest in English also decreased. Many students think that Speaking in English is very difficult, and they become lazy and indifferent. Therefore, the role of educators in creating and processing learning strategies is needed, so that students can improve their motivation and interest in learning English. One of the strategy is by role-play. This research was descriptive qualitative in used instruments consisting of observation, and test. The data was analyse by confirming the result of observation and test. Then, the researchers respond it by using relevant theories and conclude as this research result. The implementation of learning is carried out trough 6 steps; 1 Showing video to the students, 2 explaining the material based on the video, 3 giving the model text, 4 assigning the students to arrange the dialog, 5 giving the time for rehearsal, 6 role-playing the dialogue. The results show that using Role-play can motivate the students to be interest in learning Speaking English. Beside, the students could achieve better grades and they feel happy during the learning activities.
Keywords: Speaking skill; Learning strategy; role-play; students' interest